Miconazole Suppresses 27-Hydroxycholesterol-induced Inflammation by Regulating Activation of Monocytic Cells to a Proinflammatory Phenotype - Kim, Bo-Young; Son, Yonghae; Cho, Hyok-rae; Lee, Dongjun; Eo, Seong-Kug; Kim, Koanhoi (Frontiers in Pharmacology, 2021)
Miconazole is effective in treating inflammatory skin conditions and has well-established antifungal effects. To elucidate the underlying mechanisms mediating its additional beneficial effects, we assessed whether miconazole influences the inflammation induced by 27-hydroxycholesterol (27OHChol), an oxygenated cholesterol derivative with high proinflammatory activity, using THP-1 monocytic cells. Miconazole dose-dependently inhibited the expression of proinflammatory markers, including CCL2 and CCR5 ligands such as CCL3 and CCL4, and impaired the migration of monocytic cells and CCR5-positive T cells. In the presence of 27OHChol, miconazole decreased CD14 surface levels and considerably weakened the lipopolysaccharide response. Furthermore, miconazole blocked the release of soluble CD14 and impaired the transcription of the matrix metalloproteinase-9 gene and secretion of its active gene product. Additionally, it downregulated the expression of ORP3 and restored the endocytic function of THP-1 cells. Collectively, these findings indicate that miconazole regulates the 27OHChol-induced expression of proinflammatory molecules in monocytic cells, thereby suppressing inflammation in an oxysterol-rich milieu.